EDUKASI MENJAGA POSTUR DAN MENCEGAH SKOLIOSIS (POSKOLIOSIS) PADA SISWA SD MUHAMMADIYAH KLECO YOGYAKARTA - Lailatuz Zaidah; Hilmi Zadah Faidlullah; Nor Faizah Kaeni (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Background: A community service activity was conducted in August 2025 focusing on education about maintaining posture and preventing scoliosis (Poskoliosis) among students at SD Muhammadiyah Kleco, Kotagede, Yogyakarta. Objective: This activity aimed to improve the understanding of students and teachers regarding good posture and postural disorders in children. It also served as a collaborative effort between university lecturers and the school to foster public concern, awareness, understanding, and skills in detecting postural abnormalities. Method: This community service activity was carried out through a socialization/workshop program using lectures, discussions, and practical training on how to examine scoliosis in children. The results showed an improvement in students’ and teachers’ understanding of maintaining proper posture and preventing scoliosis disorders.